The impact of the constitutional reform on the internal political processes in Georgia at the beginning of the XXI century - B. G. Koybaev; Yu. V. Usova; V. Ch. Revazov (Современная наука и инновации)
The article analyzes the internal political processes in Georgia, accompanied by the constitutional reform carried out in the republic in 2009-2010. It is emphasized that she thoroughly modified the structure of state power, regulated the relationship between the legislative and executive authorities. At the same time, maintaining a balance between these two branches of government was not possible without a strong and independent judicial system. Based on this, the new version of the Constitution took into account the recommendations on the reform of the judicial system received from the Venice Commission. Based on the materials published in 2014 on the implementation of the state program for reforming the political system in Georgia, it followed that after the amendments to the Constitution, the Supreme Council of Justice of the Republic acquired a much more transparent and democratic appearance. In general, within the framework of the Euro-Georgian Association, special attention was paid to the problems of reforming the judicial system in Georgia. In the course of judicial reforms, it was necessary to solve important tasks related to a fair trial, conducting independent investigative measures, etc. The established independent judicial system was supposed to be an indicator of the functioning of democratic institutions in the republic. The concept of military reform was also developed, which provided for the creation of the institution of military service and the adoption of regulators that would facilitate its liberation from political influence. Finally, in 2014, on the proposal of the Government, the Parliament adopted a bill on the elimination of all forms of discrimination. In conclusion, the paper concludes that the constitutional reform played an important role, contributing to the reform of the political system, further integration of the republic into European structures.